Biomechanical Analysis of Pointing Motion in Petanque Sport - Kamaruddin, Ilham; Harris, Andi Sri Astrini; upa, Andika Tandi; Rio, Andi; Fitri, Airin Deasa (Jurnal Pendidikan Jasmani (JPJ), 2024)
Petanque is a type of ball game sport where the goal of this game is to throw an iron ball (bosi) as close as possible to a wooden ball (boka) as a target with both feet inside a small circle called a circle. The purpose of the study was to analyze the biomechanics of pointing motion in the sport of petanque which is divided into three parts, namely the prefix, execution, and end. This research is a quantitative study with a descriptive analysis approach method. The method used is using the survey method of the pointing throw test and the video recording documentation method, analyzing the video using kinovea software. The results of the biomechanical analysis of pointing motion data on South Sulawesi PON athletes produce an arm backswing angle of 55 O - 60 O and the right arm release angle of 78 O - 90 O which produces a ball height of 1.00 - 1.77 meters.